Deep Insight into Electrochemical Kinetics of Cowpea‐Like Li3VO4@C Nanowires as High‐Rate Anode Materials for Lithium‐Ion Batteries. Issue 15 (10th July 2019) - Yang, Yang; Zhao, Min; Xiong, Jian; Geng, Hongbo; Zhang, Yufei; Li, Cheng Chao; Zhao, Jinbao
Abstract: Owing to the high theoretical capacity (394 mAh g −1 ) and appropriate lithiation voltage (0.5–1.0 V vs Li + /Li), Li3 VO4 is highly regarded as an attractive anode candidate for high‐safety lithium‐ion batteries. However, its high‐rate performance is seriously restricted by the sluggish electrode kinetics. To address these problems, we synthesize cowpea‐like Li3 VO4 @C nanowires through a facile electrospinning method. In this well‐designed structure, Li3 VO4 nanocrystals are uniformly encapsulated in conductive carbon nanofibers just like peas in their pods. The 1D morphology with high electronic conductivity can afford high Li + ions diffusion rate and fast surface charge storage mechanism, leading to significantly enhanced electrochemical kinetics. Even after 1000 cycles at 2 A g −1, the reversible capacity of cowpea‐like Li3 VO4 @C nanowires can be maintained at 318.0 mAh g −1 without obvious capacity decay. Abstract : Peas in a pod : Cowpea‐like Li3 VO4 @C nanowires are prepared through a simple electrospinning method. In this special structure, Li3 VO4 nanoparticles are uniformly encapsulated in the carbon nanofibers just like peas in their pods. Benefiting from the characteristic 1D nanowire morphology and uniform carbon coating layer that greatly enhances the electronic conductivity as well as shortens the transport pathways of Li + ions, the cowpea‐like Li3 VO4 @C exhibits excellent cycling stability and remarkable rate performance.